Microscale Petrographic, Trace Element, and Isotopic Constraints on Glauconite Diagenesis in Altered Sedimentary Sequences: Implications for Glauconite Geochronology. (13th April 2023) - Rafiei, M.; Lӧhr, S. C.; Alard, O.; Baldermann, A.; Farkaš, J.; Brock, G. A.
Abstract: Glauconite is an authigenic clay mineral that is common in marine sedimentary successions. Dating of glauconite to determine the depositional age of sedimentary sequences has a long history but has fallen into disfavor due to the difficulty of obtaining "pure" glauconite separates. Recent advances in sedimentary petrography and reaction cell mass spectrometry permit rapid in situ Rb‐Sr dating of carefully screened glauconite grains. However, glauconite remains susceptible to burial alteration so that successful application of in situ Rb‐Sr glauconite geochronology requires improved, microscale constraints on the impact of postdepositional alteration on glauconite Rb‐Sr systematics and articulation of robust criteria for identifying grains suitable for geochronology. Here, we address these questions by combining SEM‐EDS mineral mapping, geochemical characterization, and in situ Rb‐Sr dating of glauconite grains in partially altered lower Cambrian sedimentary sequences from the Arrowie and Amadeus basins in Australia. Our approach provides information at high spatial resolution, representing new insights into the interplay between source material, burial fluids, and diagenetic processes. Among the different glauconite classes, which we classify based on alteration and inclusion type, only the primary apatite‐bearing "pristine" glauconite returns an age within the error of the expected stratigraphic age. We attribute the preservation of a depositional Rb‐Sr age to the influence of Sr‐rich, alteration‐resistant apatite and the limited permeability of the clay‐rich strata hosting these grains. We conclude that our combined petrographic–geochemical screening approach holds considerable potential for identifying the best preserved glauconite grains for in situ Rb‐Sr geochronology. Key Points: New technology permits in situ Rb‐Sr dating of carefully screened glauconite grains Apatite resists Sr exchange, and apatite‐bearing glauconite preserves primary Rb‐Sr age Young and old ages are due to Sr exchange with burial fluids and uptake of radiogenic Sr in secondary carbonate inclusions, respectively